Study of the socio-psychological significance of the tolgau Aktamberdy Saryuly - Tashimbayeva, С.Ж. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2020)
The article analyzes the hermeneutic nature of the manifestation of sociopsychological consciousness in the thoughts of Aktamberdy Saryuly. It is necessary to pay attention to other methods of studying his works: to awaken and motivate the human mind in the thoughts of zhyrau, to analyze the lyrical nature of the poetic “I” and inner sadness. Examining the connection between the poetic «I» and inner sadness, we studied the issue of romantic, psychological «poetic loneliness» in the thoughts of Aktamberdy. The loneliness, life and spiritual loneliness of the poet are the motives of his work. Until now, the thoughts of zhyrau have been studied in a didactic and philosophical direction, issues of national mentality, national color in his poems, which were the main feature of zhyrau, were considered. Continuing this opinion in this article, we made a psychological and analytical analysis and theoretical assessment.